Some thoughts on informalit y and regularizati on of urban lands (2009)
The causes of urban irregularity in Latin American cities, the implemented policies for regularization of the land and the effect of these policies on the issue of informal urban development, poverty and the land market are analyzed in this text. The problems of irregular / illegal / informality in Latin America have different shapes and dimensions depending on the country and on each level of development. Since 1960, but more strongly since the early eighties, governments, some in more degree than others, have implemented standards and land regularization programs. Twentyfive years of land policies and programs allow reviewing the quantitative and qualitative results of such programs, therefore achieving an overview of current conditions and identification of barriers that do not allow the overcoming of urban irregular / illegal / illegality conditions in Latin America.